Muscle use during double poling evaluated by SEMG and positron emission tomography - Bojsen-Moller, J.; Losnegard, T.; Santer, S.; Kemppainen, J.; Viljanen, T.; Kalliokoski, K.; Hallén, J. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
Muscle use during cross-country skiing (XCS) has mainly been evaluated by use of surface EMG (SEMG). During complex dynamic contractions the SEMG methodology has certain inherent limitations (1). Positron emission tomography (PET) presents an alternative method to acquire detailed information about muscle use during human movement (2), however, the two methods have not previously been combined. The purpose of the present study was to evaluate muscle use during double poling (DP), and more specifically to compare PET and SEMG data obtained during DP.